Mitochondrial dysfunction and its association with age-related disorders - Somasundaram, Indumathi; Jain, Samatha M.; Blot-Chabaud, Marcel; Pathak, Surajit; Banerjee, Antara; Rawat, Sonali; Sharma, Neeta Raj; Duttaroy, Asim K. (Frontiers in Physiology, 2024)
Aging is a complex process that features a functional decline in many organelles. Various factors influence the aging process, such as chromosomal abnormalities, epigenetic changes, telomere shortening, oxidative stress, and mitochondrial dysfunction. Mitochondrial dysfunction significantly impacts aging because mitochondria regulate cellular energy, oxidative balance, and calcium levels. Mitochondrial integrity is maintained by mitophagy, which helps maintain cellular homeostasis, prevents ROS production, and protects against mtDNA damage. However, increased calcium uptake and oxidative stress can disrupt mitochondrial membrane potential and permeability, leading to the apoptotic cascade. This disruption causes increased production of free radicals, leading to oxidative modification and accumulation of mitochondrial DNA mutations, which contribute to cellular dysfunction and aging. Mitochondrial dysfunction, resulting from structural and functional changes, is linked to age-related degenerative diseases. This review focuses on mitochondrial dysfunction, its implications in aging and age-related disorders, and potential anti-aging strategies through targeting mitochondrial dysfunction.